A Linguagem Lúdica no Desconcerto do Evangelho / Ludic language in the Gospel’s disconcert - Rego, Andréia Régia Nogueira do; Piteri, Sônia Helena de Oliveira Raymundo (Revista de Letras, 2007)
Em O Evangelho segundo Jesus Cristo (1991), José Saramago apresenta novas possibilidades de absorver o mito judaico-cristão, bem como transforma valores absolutos em relativos ao sugerir a manipulação exercida pelas instituições, mais precisamente pelo “cristianismo institucional”. Este trabalho perscrutará o discurso ficcional numa relação contrapontística com o discurso bíblico. O confronto entre o discurso ficcional e o religioso será revelador dos recursos utilizados pelo escritor no seu processo de transfiguração dos textos sagrados, manifestando, assim, sua postura critica em relação à concepção de verdade proposta pelos dogmas católicos. Paralelamente, será realçada a figura do narrador, a que denominamos “senhor da narrativa”, e analisando o ato de enunciação de Saramago, cujo romance problematiza a sua própria matéria, questionando o poder da palavra em encobrir/descobrir os acontecimentos.In O Evangelho segundo Jesus Cristo (1991), José Saramago presents new possibilities of absorbing the Christian-Jewish myth as well as possibilities of transforming absolute values into relative ones when he suggests manipulation carried out by institutions, more specifically by “the institutional christianity”. This paper will analyse the fictional discourse in a counterpoint relation with the biblical discourse. The confront between the fictional and the religious discourses will be the means of revealing the resources used by the fictional and the religious discourse will be the means of revealing the resources used by the writer in his transfiguration process of the sacred text showing therefore his critical point of view to the truth concept proposed by the catholic dogma. Parallel to it, the narrator’s figure that will be named “the narrative Lord” wil be stressed, and the enunciation act in Saramago will be also analysed to show that the novel makes a problem of its own matter – the word, by questioning its power of hidinf/revealing what happens.